Orientation-Specific Computation in Stereoscopic Vision - Farell, Bart (Society for Neuroscience, 2006)
The left and right eyes receive subtly different images from a visual scene. Binocular disparities of retinal image locations are correlated with variation in the depth of objects in the scene and make stereoscopic depth perception possible. Disparity stereoscopically specifies a stimulus; changing the stimulus in a way that conserves its disparity leaves the stimulus stereoscopically unchanged. Therefore, a person’s ability to use stereo to see the depth separating any two objects should depend only on the disparities of the objects, which in turn depend on where the objects are, not what they are. However, I find that the disparity difference between two stimuli by itself predicts neither stereoacuity nor perceived depth. Human stereo vision is shown here to be most sensitive at detecting the relative depth of two gratings when they are parallel. Rotating one grating by as little as 10° lowers sensitivity. The rotation can make a perceptible depth separation invisible, although it changes neither the relative nor absolute disparities of the gratings, only their relative orientations. The effect of relative orientation is not confined to stimuli that, like gratings, vary along one dimension or to stimuli perceived to have a dominant orientation. Rather, it is the relative orientation of the one-dimensional components of stimuli, even broadband stimuli, that matters. This limit on stereoscopic depth perception appears to be intrinsic to the visual system’s computation of disparity; by taking place within orientation bands, the computation renders the coding of disparity inseparable from the coding of orientation.